Nonpharmacological management of atopic dermatitis - Sebastian Criton; Geethu Gangadharan (Wolters Kluwer Medknow Publications, 2017)
Atopic dermatitis is an immunologically mediated chronic inflammatory disease which cannot be controlled always with topical agents. Systemic drugs play important role in these difficult to manage cases. Systemic agents are also important in controlling the acute flare. Unfortunately these agents are very limited in number. Moreover none of them starting from corticosteroid to azathioprine can provide complete cure. Continuous research is unfolding different aspects of AD pathogenesis which was not known previously. Scientists are engaged in developing newer molecules targeting those novel pathological pathways thus adding in the armamentarium of existing drugs. This article is dedicated to current systemic treatment options available with their individual merit and demerit along with recent advances in this field.